A Rubric Design: Assessing Innovation During Teaching Practicum - Ramiaida Darmi; Hayati Ismail; Sarifah Nurhanum Syed Sahuri; Siti Rosilawati Ramlan; Noor Saazai Mat Saad; Mohd Muzhafar Idrus; Fariza Puteh Behak (Usim Press, 2024)
Volume :1 No: 2 (page: 91–102)